Analisa Dampak Lingkungan Pengolahan Air Bersih Instalasi Pengolahan Air (IPA) Menggunakan LCA dan AHP - Aditya Yoga Pratama; Inggit Marodiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Water treatment at the Kedunguling Water Treatment Plant (WTP) has an impact on the environment due to the use of chemicals during the water purification process. This study aims to determine the environmental impact of the Kedunguling water treatment plant and determine the best alternative to reduce the impact on the environment at the Kedunguling water treatment plant. The method used to analyze environmental impacts is Life Cycle Assessment (LCA) and AHP to provide the best alternative. The results obtained are the impact of the flocculation process on water treatment provides the highest global warming impact, which is 71244.1 kg CO2-eq while the sedimentation process provides the highest eutrophication impact of 1.86E-03 kg CO2-eq. The best alternative to minimize the environmental impact caused by the water treatment process is to maximize sudge treatment before discharging into the river with a weight percentage of 42%.